Investigating Leakage from Spurious Emissions via Accidental Electric Antennas - Kustov, A. K.; Zabolotnyi, V. I. (ХНУРЕ, 2025)
Ensuring the information security of electronic computing equipment is a critical task for technical protection complexes. A significant threat is posed by spurious electromagnetic emissions. While previous research focused on the magnetic field component's re-radiation, the channel formed by the electric field remains understudied. This report aims to build a quantitative model of this leakage channel, where the electric field from main technical equipment induces a signal in a conductor acting as an accidental antenna formed by auxiliary systems. The study covers induction, re- radiation, and their impact on the hazardous zone. The proposed quantitative approach shows that ignoring this channel can lead to an underestimation of the hazardous zone's radius by fifty percent or more. The results prove the necessity of a comprehensive analysis of both electromagnetic field components for an adequate threat assessment and the implementation of more effective security methods.
Keywords: information security; spurious electromagnetic emissions; technical information leakage channel; re-radiation